A new approach to laparoscopic skill assessment: Motion smoothness and bimanual coordination - Farzad Aghazadeh; Bin Zheng (Laparoscopic, Endoscopic and Robotic Surgery)
Objective: Reliable and objective methods for assessing surgical skill are essential for improving surgical skills and clinical outcomes. While conventional methods rely on subjective evaluations, motion analysis can offer a quantitative alternative. This study aims to use motion tracking data to analyze the motion smoothness and bimanual coordination of various surgical skill levels during laparoscopic surgery. Methods: The participants were recruited and grouped into an expert group, an intermediate group, and a novice group on the basis of their experience with laparoscopic surgery. They completed peg transfer, bimanual peg transfer, and rubber band translocation tasks. Motion smoothness was assessed via logarithmic dimensionless tooltip motion jerk, and the dynamic time warping metric of tooltips velocities was employed to assess bimanual coordination. Results: Seventeen participants, with four experts, five intermediates, and eight novices, were included. Compared with novices, the experts exhibited smoother motion in both the dominant hand (peg transfer: 16.30 vs. 18.05, p = 0.004; bimanual peg transfer: 15.21 vs. 17.45, p = 0.004; rubber band translocation: 14.32 vs. 15.87, p = 0.004) and non-dominant hand (peg transfer: 16.32 vs. 18.22, p = 0.004; bimanual peg transfer: 15.32 vs. 17.52, p = 0.004; rubber band translocation: 14.33 vs. 15.77, p = 0.004), and superior bimanual coordination (peg transfer: 8.77 m/s vs. 13.28 m/s, p = 0.004; bimanual peg transfer: 6.29 m/s vs. 11.13 m/s, p = 0.004; rubber band translocation: 4.50 m/s vs. 7.13 m/s, p = 0.004) across all tasks. They also outperformed intermediates in motion smoothness in the non-dominant hand and bimanual coordination in the peg transfer (16.32 vs. 17.35, p = 0.016; 8.77 m/s vs. 11.89 m/s, p = 0.016) and bimanual peg transfer (15.32 vs. 16.22, p = 0.016; 6.29 m/s vs. 8.63 m/s, p = 0.032) tasks. Similarly, intermediates demonstrated smoother motion in the non-dominant hand (peg transfer: 17.35 vs. 18.22, p = 0.002; bimanual peg transfer: 16.22 vs. 17.52, p = 0.002) and dominant hand (bimanual peg transfer: 16.06 vs. 17.45, p = 0.011), and better bimanual coordination (peg transfer: 11.89 m/s vs. 13.28 m/s, p = 0.002; bimanual peg transfer: 8.63 m/s vs. 11.13 m/s, p = 0.002) than novices did in these tasks. Conclusion: This study revealed that motion smoothness and bimanual coordination are capable of facilitating surgical skill differentiation across various skill levels. These findings underscore the utility of motion metrics for objective surgical skill assessment, potentially reducing the subjectivity, bias, and associated costs of conventional assessment approaches.